Digital national currency paradigm: risks and benefits - I. B. Rodina (Вестник университета, 2022)
The article analyses the specifics and aspects of the digital national currency in the digital economy to substantiate the evidence of the cardinal transformation of the national market of means of payment of any particular country and the modernisation of the actions of all subjects of the money market. The realisation of this goal may be possible by setting and performing the following tasks: assessment of the role and place of non-cash payments; proof of the collapse in demand for cash; proof of the legitimacy, necessity and features of the formation of a fundamentally new digital modification of central banks’ money. The methodological apparatus used in carrying out the research is described and justified. The phenomenon of the national digital currency is innovative; therefore, it is ambiguously perceived by central banks, international organisations, business representatives, the scientific community, and the population. Each central bank evaluates the innovative advantages of the digital mechanism as a result of testing pilot projects of various modifications of digital national currencies. Any digital currency of a particular country has specific features of calculations dictated by national features of the monetary system, conditions, goals and instruments of monetary policy. Most regulators evaluate the agreed options, study the potential consequences of using this mechanism, resort to the services of public experts, take into account the achievements of foreign specialists. As a result of the study, it was concluded that the central bank’s digital currency acts as a breakthrough technology of macroeconomic policy that neutralises the macroeconomic risks of cross-border payments.